Anisotropic penetration depth measurements of high-T-c superconductors - Panagopoulos, C; Cooper, JR; Xiang, T; Peacock, G; Gameson, I; Edwards, P; Schmidbauer, W; Hodby, J (1997)
A systematic study of the anisotropic magnetic penetration depth λ for several high-Tc superconductors is presented. It is shown that the existence of the linear term in the low temperature in-plane penetration depth is independent of the number of CuO2 planes per unit cell, the carrier concentration and the anisotropy. The anisotropy, however, is found to have strong effects in the out-of-plane component. The effects of Zn substitution on λ and the importance of the CuO2 planes for dx2_y2 pairing are discussed.